An electrostatic switching mechanism to control the lipid transfer activity of Osh6p - Lipp, Nicolas-Frédéric (Nat Commun, 2019)
A central assumption is that lipid transfer proteins (LTPs) bind transiently to organelle membranes to distribute lipids in the eukaryotic cell. Osh6p and Osh7p are yeast LTPs that transfer phosphatidylserine (PS) from the endoplasmic reticulum (ER) to the plasma membrane (PM) via PS/phosphatidylinositol-4-phosphate (PI4P) exchange cycles. It is unknown how, at each cycle, they escape from the electrostatic attraction of the PM, highly anionic, to return to the ER. Using cellular and in vitro approaches, we show that Osh6p reduces its avidity for anionic membranes once it captures PS or PI4P, due to a molecular lid closing its lipid-binding pocket. Thus, Osh6p maintains its transport activity between ER- and PM-like membranes. Further investigations reveal that the lid governs the membrane docking and activity of Osh6p because it is anionic. Our study unveils how an LTP self-limits its residency time on membranes, via an electrostatic switching mechanism, to transfer lipids efficiently.